Style trends in Soviet architecture of the 1930s - Barkhin, Andrey (project baikal, 2023)
In 1932, the competition for the Palace of the Soviets formally proclaimed a focus on “mastering the classical heritage”. From that moment on, Soviet architects turned with passion to Italian Renaissance motifs and the tradition of domestic pre-revolutionary architecture. However, in 1934, the Palace of Soviets was accepted for construction in an innovative, ribbed style and Art Deco forms. In those years, that kind of architecture was developing abroad as well. New York and Chicago became centres of rapid growth in the number of skyscrapers in Art Deco style; the new centre of Washington was worked out in Neoclassical style. All this allows us to record the phenomenon of style parallelism in the Soviet and foreign architecture of the 1930s.